Role of integrated farming systems in land degradation control and plant diversity enhancement: A case of northeast Thailand - Ritdecha Chuanrum; Rajendra P. Shrestha (Farming System)
While agriculture provides livelihood to rural poor, it has also been the reason of land degradation and biodiversity loss over time. Although the Integrated Farming Systems (IFS) are promoted to address these issues, their adoption among local farmers has been slow. The adoption is contextual affected by local conditions and factors. To understand the role of IFS in land degradation control and plant diversity enhancement, the objective of this study was to examine the determinants of farmers’ adoption of IFS practices and investigate the role of IFS in land degradation control and plant diversity enhancement on farmlands. Combining socioeconomic survey, econometrics, and ecological assessment techniques, the data representing different types of land degradation and sub-plot level plant diversity were collected using both farmer interviews and field measurements for two groups farmers, those who have adopted some sort of IFS, and other who have not. When compared with non-IFS as base category, the results indicated that education and income positively influenced IFS adoption with a marginal effect of 0.035 and 0.001, respectively, contrasting with the negative impact of landholding size with a marginal effect of -0.081. IFS adoption led to reduced land degradation of various forms as perceived by the farmers, particularly reduced soil acidification with marginal effect of 2.52, soil erosion (2.071), and enhanced plant diversity as shown by the indices, Shannon-Weiner – 1.94, Inverse Simpson – 6.14, species richness – 10.65 for IFS plots compared to 1.03, 2.28, 5.06, respectively for the non-IFS plots. The findings offer valuable insights for agricultural extension authorities and local farmers, emphasizing the benefits of IFS practices. The study also underscores not only the environment gains of IFS practices but also holds the potential for long-term economic and ecological benefits.